Implementasi Peraturan Bupati Nomor 298 Tahun 2023 tentang Rencana Pengelolaan Risiko Banjir Daerah Kabupaten Serang Tahun 2023-2027 oleh DPUPR (Studi Kasus Desa Ketos, Kecamatan Kibin) - Firlyn Solehatunnisa; Rizki Amilia; Try Adhi Bangsawan (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of Serang Regent Regulation Number 298 of 2023 concerning the 2023-2027 Regional Flood Risk Management Plan for Serang Regency by the Public Works and Spatial Planning Agency (DPUPR), using a case study in Ketos Village, Kibin District. The study is motivated by the persistence of flooding which causes infrastructure damage and disrupts community activities and the indication that flood risk management policies are not yet being implemented optimally. A qualitative method with a descriptive approach was employed. Data were collected through observation, in-depth interviews, documentation, and literature review, and subsequently analyzed using data reduction, data presentation, and conclusion drawing. The policy implementation analysis is based on George C. Edward III’s model, covering communication, resources, disposition, and bureaucratic structure. The results indicate that policy implementation has been carried out through the normalization of drainage channels, the upgrading of flood control infrastructure capacity, inter-agency coordination, and public outreach. However, implementation still faces obstacles such as budget constraints, suboptimal inter-agency coordination, low community participation, and land-use changes that increase flood risk. Therefore, strengthening stakeholder collaboration, enhancing institutional capacity, and optimizing infrastructure management and community participation are essential to achieving the policy objectives sustainably.